Peningkatan Iklim Sekolah yang Kondusif dengan Medan Sosial yang Generatif - Nurhayati (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
The school climate plays a crucial role in shaping students' learning experiences. This article examines the school climate in Indonesia, emphasizing the importance of a healthy, safe, and supportive learning environment. Based on literature and empirical data, the study found that, despite significant efforts to improve the quality of the school climate, challenges remain. Key issues requiring attention include the quality gap in education between urban and rural areas, lack of physical facilities, bullying, and students' emotional well-being. A conducive school climate is a prerequisite for optimal learning. This article discusses the relationship between the social environment in schools and the formation of a climate that supports learning. A generative social field is created by the active and authentic presence of educators and other adults in schools. These individuals play a crucial role in fostering a safe and productive learning environment for students. The concept of "showing up" or meaningful presence is used to understand the role of teachers and staff in creating this social field. This paper emphasizes that learning activities are social by nature and that how teachers present themselves greatly influences students' readiness to learn.